Use of implantable meshes for augmented rotator cuff repair: a systematic review and meta-analysis. Issue 12 (7th December 2020) - Baldwin, Mathew; Nagra, N S; Greenall, Gemma; Carr, Andrew J; Beard, David; Rees, J L; Rangan, Amar; Merritt, Naomi; Dritsaki, Melina; Hopewell, Sally; Cook, Jonathan Alistair
Abstract : Objective: To appraise studies reporting on clinical effectiveness and safety of surgical meshes used to augment rotator cuff repairs (RCRs). Design: Systematic review and meta-analysis. Data sources: MEDLINE, Embase and Cochrane databases were searched between April 2006 and April 2020. Eligibility criteria: All studies evaluating adults (≥18 years) undergoing RCR were considered. There were no language restrictions. Data extraction and synthesis: Screening, data extraction and quality appraisal were conducted by two independent reviewers. Meta-analysis was conducted using a random-effects models if ≥2 comparative studies reported the same outcome measure. Risk of bias assessment was undertaken for randomised (RoB2, Cochrane) and comparative studies (ROBINS-I, Cochrane). Results: We included 60 studies, consisting of 7 randomised controlled trials, 13 observational comparative studies and 40 observational case series. All comparative studies reported on shoulder-specific functional outcome scores, 18 on the radiographic occurrence of re-tear and 14 on pain score metrics. All studies contained some risk of bias. Compared with non-augmented repair, a small improvement in shoulder-specific function or pain scores was observed for synthetic patches with a mean improvement of 6.7 points on the University of California Los Angles (UCLA) shoulder score (95% CI 0.1 to 13.4) and 0.46 point reduction on the Visual Analogue Scale (95% CI −0.74 to −0.17), respectively. A reduced likelihood of radiologically observed re-tear was observed for synthetic (risk ratio (RR) 0.41, 95% CI 0.27 to 0.61) and allograft (RR 0.34, 95% CI 0.18 to 0.65) patches. A total of 49 studies reported on the occurrence of complications. Slightly higher crude complication rates were observed following patch-augmented repair (2.1%) than standard repair (1.6%). Conclusions: While several studies suggest a decreased failure rate and small improvements in shoulder function and pain following augmented RCR, a paucity of rigorous clinical evaluation, for both effectiveness and safety, prevents firm recommendations. Prospero registration number: CRD42017057908.